Accelerator MS: its role as a frontline bioanalytical technique. (December 2011) - Seymour, Mark A
Accelerator MS (AMS) is an ultrasensitive technique that can be used to quantify 14 C in biological samples. Prior to analysis, the carbon in samples is selectively isolated, with the result that the technique is independent of compound structure and nonsusceptible to matrix effects. AMS is a tracer technique and therefore can be used to quantify all compound-related material without the need to develop extraction or chromatographic separation methods. Thus AMS has some distinct advantages over conventional assay techniques, such as LC–MS/MS. AMS also complements conventional techniques, facilitating innovative, cost-effective clinical study designs. Thus, metabolism data can be obtained from early clinical trials, identifying any human metabolites that may raise safety concerns. By administration of an intravenous 14 C microtracer dose concomitantly with an extravascular dose of nonradiolabeled compound, AMS can also be used to determine absolute bioavailability and intravenous pharmacokinetic parameters without the need for intravenous toxicology or formulation development.